The threat to national security and private data collection of the state in the eyes of Human Rights - Gielnik, Romane (Wydawnictwo C.H. Beck, 2022)
In this article, it is debated on how the collection of individual’s private data by the State affects Human Rights. The peculiar context in which intelligence took its place in our societies has created all its traits and aspects we have today. It has been developed in the age of the Cold War and the War on Terror, a very politically uncertain part of history, which led most governments to fear for their safety. Also, the simultaneous rise of the Digital Age, since the 1950s, nourished this common fright: a new, unknown and unmastered tool was being spread in the hands of all individuals. Two main issues were then confronting each other: the need to preserve the individuals’ security as well as their right to privacy and others Human Rights. The interests seemed to oppose each other: to grant a total right to privacy to individuals rhymed with a lack of surveillance of the State on individuals and hence the inability to protect their citizens, when the collection of private state seemed to intrude the right to privacy and so weaken democracy, freedom of opinions and others. If the two notions are opposing, it does not, however, necessarily mean they are contradicting each other: norms should evolve according to the society they serve.
Keywords: National Security; Digital Age; Private Data; Surveillance; Human Rights; Democracy